Leadership and Innovation in Public Sector Organizations: A Case-Study of the Emirate of Dubai - Hashmi, M. Anaam; Al Maazmi, Sabah (Archives of Business Research, 2022)
This qualitative study is based on extensive interviews from government and semi-governments organization in the Emirate of Dubai. The study found a strong relationship between leadership and innovation in public-sector organizations of Dubai. Creation of innovation culture has a positive impact on organizational performance as well.